Thoracic fluid content as a novel and rapid diagnostic indicator of secondary capillary leak syndrome in pediatric patients post-cardiopulmonary bypass - Huo, Junming; Cheng, Jie; Liu, Chengjun; Fu, Yueqiang; Xu, Feng; Li, Jing (Frontiers in Pediatrics, 2025)
ObjectiveCapillary leak syndrome (CLS) is an urgent problem in postoperative patients, is challenging to diagnose early, and has a poor prognosis. We investigated a quick and convenient diagnostic indicator of secondary CLS in children after cardiopulmonary bypass (CPB).MethodsWe conducted this single-center, observational, prospective study in the Department of Critical Care Medicine at the Children's Hospital of Chongqing Medical University. All the data were collected within 24 h after cardiopulmonary bypass (CPB). The secondary CLS risk factors were determined using univariate and multivariate logistic regression analysis, and the cut-off point of secondary CLS was found by receiver operating characteristic (ROC) analysis.ResultsOur study included two hundred four pediatric patients in the PICU after cardiopulmonary bypass (CPB). 42.65% (87/204) of patients were diagnosed with secondary CLS. The incidence of acute kidney injury (AKI) was 36.76% (75/204), and the mortality was 5.39% (11/204). Logistic analysis indicated that a pulmonary exudation on chest radiograph, a high thoracic fluid content (TFC) and a higher vasoactive inotropic score (VIS) were independent risk factors for secondary CLS [odds ratio [OR] 23.62, 95% confidence interval [CI] 7.20–90.41, p < 0.001; OR 1.08, 95% CI 1.02–1.16, p = 0.010; OR 1.06, 95% CI 1.01–1.14, p = 0.049; respectively]. According to the ROC analysis, the cut-off point for the TFC was 52 (Ω−1).ConclusionsThe TFC plays a key role in the early prediction of secondary CLS in children after CPB, and this novel indicator may help clinicians initiate intensive treatment as early as possible.